Analysis of essential gene changes in MRSA and non-MRSA strains inhibited by methanolic extract correlated to membrane permeabilising peptide - Shamsudin, M.; Mohamed Alipiah, Norfarrah; Neela, Vasantha Kumari; Md Yusoff, Fatimah; Arshad, Aziz (Elsevier, 2007)
In this study, a methanolic extract derived from a marine organism was investigated for the effect on the growth of MRSA resistant to b-lactam antibiotics. The nucleotide sequence changes of essential genes inclusive of mecA, mecR1, 16sRNA, mprF and msR of the inhibited MRSA strains were determined. A potential antibacterial peptide with activity on permeabilising the membrane of MRSA strains was investigated through a cellular bioassay.